2020
DOI: 10.1128/jcm.01438-20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Self-Collected Saliva by Quantitative Reverse Transcription-PCR (RT-qPCR), Direct RT-qPCR, Reverse Transcription–Loop-Mediated Isothermal Amplification, and a Rapid Antigen Test To Diagnose COVID-19

Abstract: Background: The clinical performance of six molecular diagnostic tests and a rapid antigen test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were clinically evaluated for the diagnosis of coronavirus disease 2019 (COVID-19) in self-collected saliva. Methods: Saliva samples from 103 patients with laboratory-confirmed COVID-19 (15 asymptomatic and 88 symptomatic) were collected on the day of hospital admission. SARS-CoV-2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
376
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(405 citation statements)
references
References 26 publications
21
376
1
7
Order By: Relevance
“…2020 ; Iwasaki et al 2020 ; Jamal et al 2020 ; Kim, Lee, et al 2020 ; McCormick-Baw et al 2020 ; Migueres et al. 2020 ; Nagura-Ikeda et al 2020 ; Pasomsub et al 2020 ; Williams et al 2020 ; Wyllie et al 2020 ). Most of these studies reported the results of analyses conducted with small- and medium-sized patient cohorts (i.e., 200 subjects or fewer), although studies with larger cohorts (i.e., about 1,000 subjects) have been recently published ( Caulley et al 2020 ; Zhu, Guo, et al 2020 ).…”
Section: The Detection Of Sars-cov-2 In Salivamentioning
confidence: 99%
See 2 more Smart Citations
“…2020 ; Iwasaki et al 2020 ; Jamal et al 2020 ; Kim, Lee, et al 2020 ; McCormick-Baw et al 2020 ; Migueres et al. 2020 ; Nagura-Ikeda et al 2020 ; Pasomsub et al 2020 ; Williams et al 2020 ; Wyllie et al 2020 ). Most of these studies reported the results of analyses conducted with small- and medium-sized patient cohorts (i.e., 200 subjects or fewer), although studies with larger cohorts (i.e., about 1,000 subjects) have been recently published ( Caulley et al 2020 ; Zhu, Guo, et al 2020 ).…”
Section: The Detection Of Sars-cov-2 In Salivamentioning
confidence: 99%
“…These methods allow more rapid diagnosis by direct rRT-PCR without RNA extraction. Similarly, other companies have developed rRT-PCR devices that include fully automated commercial systems that can shorten the bench time per sample by nearly 90%, reducing the possibility of mistakes during specimen handling and allowing analysis of a larger number of patients in a shorter time frame ( Chen et al 2020 ; Lippi, Mattiuzzi, et al 2020 ; Nagura-Ikeda et al 2020 ).…”
Section: Molecular-based Tests For the Detection Of Sars-cov-2 In Salmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Direct detection of SARS-CoV-2 has been proposed in scalable, rapidly deployed formats, but often suffers from low sensitivity that limits effectivity in general population testing. 9,10 Thus, the discovery of additional reagents to enable early and rapid SARS-CoV-2 detection and/or neutralization is critical.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO currently recommends RT-PCR testing using nasopharyngeal (NPS) and oropharyngeal swabs (OPS) as gold standard for SARS-CoV-2 diagnosis and for monitoring viral load [ 4 , 5 ]. OF has been suggested as an alternate clinical sample, easy and safer to collect, minimizing exposure of healthcare workers and could be useful for making a diagnosis and measuring SARS-CoV-2 viral load and viral shedding during the course of the illness and convalescence [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. To et al, demonstrated that SARS-CoV-2 was present in OF specimen of 11 out of 12 patients, with viral load being higher during the first week after symptoms onset and declining thereafter, being detectable until 25 days after symptoms onset (DSO) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%